Effect of Power to Gas on Integrated Electricity-Gas System with Uncertain Wind Generation - Gao, Han; Li, Zhengshuo (2020 IEEE 3rd Student Conference on Electrical Machines and Systems (SCEMS), 2020)
This paper studies the effect of power to gas (P2G) facilities on an integrated electricity-gas system (IEGS) to deal with the challenge of wind generation uncertainty. A commonly used steady-state dispatch model of the IEGS is first presented, where the uncertainty in the wind power is captured in the form of a versatile probability distribution model. The associated chance-constraints are thus transformed into deterministic counterparts. Then a piecewise linearization method is adopted to resolve the nonlinearity in this dispatch model. Case studies have identified that P2G facilities can convert excessive wind energy into natural gas and thus play a positive role in reducing overall operational cost, providing downward spinning reserve and enhancing the safety of an IEGS.